Folate Intake, MTHFR Polymorphisms, and the Risk of Colorectal Cancer: A Systematic Review and Meta-Analysis. (18th October 2012) - Kennedy, Deborah A.; Stern, Seth J.; Matok, Ilan; Moretti, Myla E.; Sarkar, Moumita; Adams-Webber, Thomasin; Koren, Gideon
Abstract : Background . The objective was to determine whether relationships exist between the methylene-tetrahydrofolate reductase ( MTHFR ) polymorphisms and risk of colorectal cancer (CRC) and examine whether the risk is modified by level of folate intake. Methods . MEDLINE, Embase, and SCOPUS were searched to May 2012 using the terms "folic acid, " "folate, " "colorectal cancer, " "methylenetetrahydrofolate reductase, " " MTHFR ." Observational studies were included which (1) assessed the risk of CRC for each polymorphism and/or (2) had defined levels of folate intake for each polymorphism and assessed the risk of CRC. Results . From 910 references, 67 studies met our criteria; hand searching yielded 10 studies. The summary risk estimate comparing the 677 CT versus CC genotype was 1.02 (95% CI 0.95–1.10) and for 677 TT versus CC was 0.88 (95% CI 0.80–0.96) both with heterogeneity. The summary risk estimates for A1298C polymorphisms suggested no reduced risk. The summary risk estimate for high versus low total folate for the 677 CC genotype was 0.70 (95% CI 0.56–0.89) and the 677 TT genotype 0.63 (95% CI 0.41–0.97). Conclusion . These results suggest that the 677 TT genotype is associated with a reduced risk of developing CRC, under conditions of high total folate intake, and this associated risk remains reduced for both MTHFR 677 CC and TT genotypes.